A qualitative description of nurses' problems to monitor and supervise vital signs in COVID-19 patients in isolation room - Christina, Tri Yahya; Ismail, Suhartini; Erawati, Meira (Jurnal Ners, 2022)
Introduction: Changes and deterioration of the condition of Corona Virus Disease-19 (COVID-19) patients are unknown and can even lead to the death of the patient in the isolation room. This study focuses on identifying the problem of nurses monitoring and supervising the vital signs of COVID-19 patients in the isolation room. Methods: A descriptive qualitative study was conducted in January 2022 at a private hospital in Sukoharjo, Central Java. Ten participants who met the inclusion criteria were involved through purposive sampling. The semi-structured interview guidelines were developed by the researcher, and they used them to obtain the data. Interviews were recorded using a recorder device. The data from the interviews were recorded verbatim and analyzed using inductive content analysis following Elo and Kyngas's method. The member checking and thick description were done to maintain the validity of the data. Results: Three main themes were found from the emerging data, including 1) the comparison of nurses and patients is not ideal with patients' conditions that cannot be predicted, 2) personal protective equipment (PPE) and monitoring tools have not reached the appropriateness target, and 3) the demand for high-technology vital sign monitoring devices was not feasible. Conclusions: The problems being faced by the nurses in monitoring and supervising the vital signs of COVID-19 patients in the isolation room need innovative tools. Therefore, it is important for policymakers and related parties to create high-technology solutions for the isolation rooms to improve nursing service effectively and ensure the safety for patients and the nurses.